Optimization of cable-stayed bridges: A literature survey. (November 2020) - Martins, Alberto M.B.; Simões, Luís M.C.; Negrão, João H.J.O.
Highlights: Growing interest on cable-stayed bridges optimization, with more than half of the works published in the last decade. Cable forces optimization and optimum design represent 80% of the works. Optimization was also used for SHM, assessment and identification, design and location of control devices. Footbridges, curved bridges, long-span bridges and multi-span bridges are attracting the interest of some researchers. Optimization under dynamic actions, sustainability, resilience and robustness are of major concern in future developments. Abstract: This literature survey concerns the application of optimization techniques to cable-stayed bridges. A search within the Web of Science and Scopus electronic databases was conducted, complemented by a hand search. From a total of 155 articles, 90 were chosen for a detailed review. The search results are summarized, highlighting the procedures, the main conclusions and contributions of each work. The optimization of the cable forces distribution and the optimum design through cost minimization is present in 80% of the publications. In the last decade, optimization algorithms were used for a wide range of applications, such as, the design of hybrid fiber reinforced polymeric deck and cables, structural health monitoring, assessment and identification of existing bridges, design and location of passive and active control devices to improve the dynamic performance. The detailed analysis showed that the optimization of footbridges, long-span bridges and multi-span bridges with innovative cable arrangements like crossing-cables are attracting the interest of researchers. Moreover, the optimization taking into account the wind action, the seismic action and other dynamic effects are areas of major concern in future developments.